Gestão do conhecimento na reitoria do Instituto Federal da Paraíba: diagnóstico aplicando o Modelo de Gestão do Conhecimento para a Administração Pública Brasileira – MGCAPB - Serrano, Ana Patrícia de Carvalho Farias (2019)
The present study aimed to diagnose the knowledge management in the rectory of the Federal Institute of Paraíba - IFPB, from the stages provided in the knowledge management model for the brazilian public administration - MGCAPB. Besides that, knowledge process flow mapping and the identification of facilitators and obstacles to the development and implementation of a knowledge management plan in the Institute were made. Thus, the research consisted of a case study, of applied nature and exploratory approach, which had as subjects, the managers and public servants who work in strategic sectors for the knowledge in the rectory of the IFPB. The choice of the research population took into account the enablers indicated by the mentioned model: leadership; technology, people and processes. For the collection of data, an online questionnaire containing requirements related to the assessment of knowledge management and the instruments provided in the diagnostic and planning stages of the MGCAPB was applied. It was considered, for the data analysis, in addition to the methodological procedures, the parameters prescribed in the MGCAPB. Thus, considering the theoretical reference and the results of the research, it was concluded that the IFPB's rectory is at the beginning level of maturity in knowledge management - KM, where it begins to recognize the need to manage organizational knowledge. As results of the research, the following were presented: a business case, justifying the importance of KM to the rectory of the IFPB; a knowledge management plan and; a conceptual model of information and knowledge sharing system.